Pengaruh Dewan Komisaris, Komite Audit, Ukuran Perusahaan, dan Leverage Terhadap Profitabilitas : (Studi Empiris Pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2023) - Renny Sintawati; Prita Andini (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of the Board of Commissioners, Audit Committee, Company Size, and Leverage on Profitability in Financials Banking sector companies listed on the Indonesia Stock Exchange for the 2019 – 2023 period of 105 companies. The data used in this study were obtained from financial statement data and annual reports. The population in this study are property and real estate sector companies listed on the Indonesian Stock Exchange. The sampling technique used was purposive sampling method and obtained 215 sample data from 43 companies. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22. The results of this research show that the Board of Commissioners, Audit Committee, and Leverage does not have a significant effect on Profitability, while Company Size has an effect on Profitability.